EQUINE THERAPY IN THE TREATMENT OF CEREBROVASCULAR ACCIDENT - Rodrigues do Carmo, Luana (Health and Society, 2023)
Cerebrovascular accident is the pathology with the greatest development of clinical signs and focal and/or global disturbances in brain function, with various symptoms lasting 24 hours and resulting from vascular origin. Bringing sequelae to the patient, functional, sensitive, emotional and mental. And to alleviate this damage, it is necessary for the patient to have access to all treatments aimed at their needs, observing their capabilities and potential. Physiotherapy used techniques with the aim of stimulating CNS connections, with the intention of promoting sensorial stimuli for the recovery of functional movements, and in the prevention of deformities and complications, bringing independence and better quality of life. Treatment with equine therapy will bring results in tonic adjustments, improvement in posture, balance, stimulation of tactile and visual sensibilities, body awareness and increased self-esteem, in this therapeutic method of rules and disciplines it increases the capacity for decisions and independence in different situations.